Konflik Antara Proteksionisme dan Prinsip National Treatment dalam Hukum Perdagangan Internasional (Studi Kasus: Penerapan Prinsip National Treatment dalam Kasus Sengketa Importasi Minuman Beralkohol antara Jepang dan Kanada di WTO) - Putri, Syifadilla Subagyo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the conflict between protectionist policies and the implementation of the National Treatment principle within the international trade law framework, focusing on the alcohol import dispute between Japan and Canada at the WTO. The case highlights Japan’s tension between protecting domestic industries through fiscal measures and its international obligation to treat imported goods equally. Using a normative juridical and case study approach, the analysis finds that Japan’s alcohol tax system violated Article III of GATT 1994 by indirectly discriminating against foreign products. The WTO ruling reaffirmed the importance of the non-discrimination principle as a cornerstone of fair global trade. This research emphasizes the necessity of balancing national economic protection and adherence to international trade norms to ensure a fair and sustainable multilateral trading system.